Assessment of Some Physiological, Immunological and Molecular Biomarkers in Sample of Iraqi Women Undergoing Caesarean Section and Normal Delivery - Naser, Huda Sajir; Al-Lami, Makarim Qassim; Ghazi, Haider Faisal (Iraqi Journal of Science, 2024)
Pregnancy and delivery are physiological conditions that are marked by abrupt alterations to hormones, immunological and molecular characters. The current study aimed to evaluate oxytocin (OT), prolactin (PRL), cortisol and insulin growth factor-2 (IGF-2) levels as physiological biomarkers; programmed cell death protein-1 (PD-1), programmed cell death ligand-1 (PD-L1),interleukin-6 (IL-6) as immunological biomarkers, and single nucleotide polymorphisms (SNPs; rs53576 and rs2254298) of oxytocin receptor gene OXTR as molecular factors in samples of Iraqi women undergoing caesarean section (CS) and normal delivery (ND). Blood samples were collected from 96 pregnant women at term with ages ranging between 16-43 years. Regarding the physiological biomarkers, the study findings indicated that the change in OT, cortisol and IGF-2 between CS and ND groups was not significant, While the PRL level indicated a highly significant (P≤0.001) decrease in the CS group, especially in comparison with the ND group. Immunological biomarkers demonstrated a significant (P≤05) elevation for PD-1 as well as for PD-L1 in the CS group as compared to the ND group. However, PD-1/PD-L1 ratio revealed a high significant (P≤0.001) rise in CS compared with ND. The IL-6 results revealed a significant (P≤0.001) reduction in the CS groups compared to the ND group. And  regarding the SNP of OXTR (rs53576), the findings revealed no notable association in genotypes CC, TC and TT between both groups. In addition, the mutant C allele and the wild T allele revealed no significant association between CS and ND groups [OR=1.26 (0.68-2.3%)].  The SNP results of OXTR (rs2254298) showed a high positive association (P≤0.001) in genotypes GG, AG and AA between CS and ND groups. Also, the mutant G allele and the wild A allele revealed high significance (P≤0.001) between both groups [OR=5.3 (2.8-9.76%)].